2020
DOI: 10.1093/geront/gnaa042
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Characteristics and Experiences of Black and White Caregivers of Older Americans

Abstract: Background and Objectives Racial disparities in health and socioeconomic characteristics of older adults have implications for the experiences of their family and unpaid caregivers, but knowledge to date has primarily drawn from convenience samples. Using a population-based sample, we examine associations between caregiver race and caregiving-related effects. Research Design and Methods Study participants include white (n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…Rather, robust ethics scoring would suggest little, if any, substantial differences among racial-ethnic groups. As noted by Truitt and Snyder (2020), racial diversity would be affirmed, in contrast to the racial differences reported by Fabius (2020), and as these study findings confirm. Likewise, robust ethics sites might be described as culturally competent, exhibiting respect, for example; the latter, critical for long-term care and desired (Zhang et al 2014).…”
Section: Racial-ethnic Identitysupporting
confidence: 69%
See 2 more Smart Citations
“…Rather, robust ethics scoring would suggest little, if any, substantial differences among racial-ethnic groups. As noted by Truitt and Snyder (2020), racial diversity would be affirmed, in contrast to the racial differences reported by Fabius (2020), and as these study findings confirm. Likewise, robust ethics sites might be described as culturally competent, exhibiting respect, for example; the latter, critical for long-term care and desired (Zhang et al 2014).…”
Section: Racial-ethnic Identitysupporting
confidence: 69%
“…Likewise, workers’ relationships with supervisors were important for plans to remain at work, or retention (Stone et al 2016 ; Galleta and Sparks 2012 ). These challenges, including racial and job disparities, highlighted the need to identify desirable long-term care places where employees felt good about their work (Edwards 2005 ; Fabius et al 2020 ). Moreover, these results demonstrated the identified need for ethics analyses in long-term care, affirmed by Seavy ( 2004 ) and Lesandrini ( 2016 ) and found in this paper.…”
Section: Concluding Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black caregivers are more likely than White caregivers to report positive aspects of caregiving 390 . A meta‐analysis found that Black dementia caregivers indicate slightly higher psychological well‐being than White dementia caregivers.…”
Section: Caregivingmentioning
confidence: 99%
“…Caregiving for individuals with Alzheimer's or other dementias differs between racial and ethnic groups too. These differences include the time spent on caregiving, cultural perceptions of the burden of caregiving, whether social networks provide support, and the psychological well‐being of the caregiver 384–388,390 …”
Section: Special Report: Race Ethnicity and Alzheimer's In Americamentioning
confidence: 99%